Retrospective evaluation of sedation techniques for tooth extraction in pediatric patients - Alper Alkan; Canay Yılmaz Asan; Nükhet Kütük; Dilek Günay Canpolat (Cumhuriyet University, 2018)
Objective: Due to lack of past experiences and cooperation in anxious and fearful children, tooth extraction may be difficult to manage in dentistry.  The aims of this retrospective study were to evaluate the various sedation techniques, complications and the characteristics of children whose tooth extraction were performed with deep sedation. Materials and Methods: After approval by the Local Ethics Committee, a retrospective analysis was performed using the records of 885 patients between the ages of 1-15 years, between 2012 and 2014, and treated with deep sedation for tooth extraction. The authors described the characteristics of children, the various sedation techniques and complications. Results: The mean weight of the patients was 20.09±7.3 kilogram and the mean age was 5.72±2.5 years. The mean duration of the operations was 16.14±5.4 minutes. Propofol, ketamine, propofol-ketamine combination, alfentanil, midazolam, sevoflurane inhalation, sevoflurane inhalation+propofol were used fpr the anesthesia. There were no statistically significant differences among the anesthesic agents, nausea and vomiting (p=0.09),  and sore throat (p=0.857) and arrhythmia, bronchospasm and hypoxia (p>0.05). Conclusions: We concluded that, propofol was a better option for deep sedation in pediatric dental extraction due to short duration time, rapid recovery and less nausea-vomiting. Ketamine-propofol combination may be used as an alternative to propofol alone.